2016
DOI: 10.1007/s10896-016-9804-4
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Evaluation of the Spanish Parent–Child Aggression Acceptability Movie Task in Spain

Abstract: The current study presents a preliminary evaluation of a Spanish adaptation of an implicit analog procedure, the Parent-child Aggression Acceptability Movie task (Spanish Parent-CAAM). Based on Social Information Processing theory, Spanish Parent-CAAM scores were expected to relate to self-reported PCA attitudes, negative child attributions, and child abuse risk in Spanish students; 245 undergraduates in Spain completed the Spanish Parent-CAAM along with selfreport measures of PCA attitudes, negative children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…One strategy to prevent aggression and intervene in abusive relationships has been to identify the precursors for abusive potential (Rodriguez, Gracia, & Lila, 2016), such as identifying personality characteristics or situational factors that lead to the intent to enact aggressive behaviors. For example, personality disorders such as narcissism, borderline, and sociopathic traits have been identified as prevalent among APs (Cunha Gomide, Camargo, & Ferdandes, 2016; Gordon, Stoffey, & Bottinelli, 2008; Harman & Biringen, 2016), and they are typically angry, jealous, emotionally fragile, and dependent on others (even their children) for their self-esteem.…”
Section: Family Violencementioning
confidence: 99%
“…One strategy to prevent aggression and intervene in abusive relationships has been to identify the precursors for abusive potential (Rodriguez, Gracia, & Lila, 2016), such as identifying personality characteristics or situational factors that lead to the intent to enact aggressive behaviors. For example, personality disorders such as narcissism, borderline, and sociopathic traits have been identified as prevalent among APs (Cunha Gomide, Camargo, & Ferdandes, 2016; Gordon, Stoffey, & Bottinelli, 2008; Harman & Biringen, 2016), and they are typically angry, jealous, emotionally fragile, and dependent on others (even their children) for their self-esteem.…”
Section: Family Violencementioning
confidence: 99%
“…The Spanish Parent-CAAM task has demonstrated validity in previous studies. For example, the Spanish Parent-CAAM significantly related to self-reported acceptability of physical punishment of children, attributions of children’s intention, propensity to punish children and CA potential among college students (Rodriguez et al, 2016a); with IPV perpetrators, the Spanish Parent-CAAM also related to self-reported approval of parent–child aggression and CA risk (Rodriguez et al, 2016b). Cronbach’s alpha for the Spanish Parent-CAAM in this sample was .76.…”
Section: Methodsmentioning
confidence: 99%
“…The Spanish Parent-Child Aggression Acceptability Movie Task (Spanish Parent-CAAM Task; Rodriguez, Gracia, & Lila, 2016a) is an implicit measure of acceptability of parental physical aggression toward children. This analog task is a Spanish adaptation of the original Parent-Child Aggression Acceptability Movie (PCAAM) Task (Rodriguez et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…For example, in a film that tells about the relationship between parent and child can also be used as a message that the relationship between parent and child has the characteristics of each according to their culture and environment. There are parents who punish their children for discipline, there are also parents who use communication [15]. Because a lot of films worked on for industrial purposes.…”
Section: B Local Film As Character Education Charactermentioning
confidence: 99%